1034PPhase I study of intraperitoneal TRX-E-002-1 in subjects with persistent or recurrent ovarian, fallopian tube or primary peritoneal cancer: Three-month follow-up results of the dose escalation phase. (1st October 2019) - Coward, J; Kichenadasse, G; Harnett, P; Moore, K; Barve, M; Berg, D; Garner, J; Dizon, D
Abstract: Background: The poor outcomes associated with current therapies for recurrent epithelial ovarian cancer (EOC) are thought to reflect the existence of drug-resistant ovarian cancer stem cells (OCSCs). TRX-E-002-1 is a novel, third generation benzopyran molecule that induces caspase-dependent and -independent apoptosis in CD44 positive ovarian cancer stem-like cells and CD44 negative ovarian somatic cancer cells. The dose escalation phase of a progressive design trial investigating intraperitoneal (IP)-administered TRX-E-002-1 monotherapy and in combination with standard of care for recurrent EOC (NCT02903771) has been completed with a Maximum Tolerated Dose (MTD) of 5 mg/kg established. Methods: Women with platinum resistant, persistent or recurrent EOC were enrolled into the dose escalation phase of the study (Part A) in which TRX-E-002-1 monotherapy was administered IP weekly for 2 three-week cycles, after which combination with standard intravenous chemotherapy was allowed to a maximum of 8 cycles. Subjects were followed up for 3 months after the end of treatment. The study objectives were to establish the MTD and to evaluate safety, tolerability, pharmacokinetics and anti-tumour activity of TRX-E-002-1. Results: A total of 9 subjects were evaluable for efficacy. Four of 9 patients completed 8 cycles (6 months); 2 remained progression-free at the 3-month endpoint post-treatment (9 months). Preliminary data on activity include 1 partial response (during combination treatment) and 5 patients with stable disease on monotherapy per RECIST criteria. The most common drug-related adverse events, not generally dose limiting, were abdominal pain (27%), fatigue (13%), vomiting (10%) and nausea (10%). There was limited accumulation of TRX-E-002-1 with multiple dosing across multiple concentration‐time points. PK profiles were comparable between all subjects with plasma concentrations progressively declining to < 10% maximal concentrations by 24 hours. Conclusions: IP administered TRX-E-002-1 as a first-in-class, dual acting, anti-cancer therapy has demonstrated preliminary activity for the treatment of platinum resistant ovarian cancer. Clinical trial identification: NCT02903771. Editorial acknowledgement: Dr Caroline Markey, Markey Medical Consulting. Legal entity responsible for the study: Kazia Therapeutics Limited. Funding: Kazia Therapeutics Limited. Disclosure: J. Coward: Honoraria (institution): Takeda Pharmaceuticals; Research grant / Funding (self): AstraZeneca; Leadership role, Overseas Trainee Sub-committee member: Royal Australasian College of Physicians. K. Moore: Honoraria (self), Speaker Bureau / Expert testimony, Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution): Clovis; Advisory / Consultancy, Research grant / Funding (institution): Immunogen; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Tesaro; Advisory / Consultancy: Pfizer; Advisory / Consultancy, Research grant / Funding (self): Merck; Advisory / Consultancy: Aravive; Advisory / Consultancy, Research grant / Funding (institution): OncoMed; Advisory / Consultancy: Samumed; Advisory / Consultancy: Eisai; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Genentech/Roche; Advisory / Consultancy: Janssen; Advisory / Consultancy: Cue; Research grant / Funding (self): Lilly; Research grant / Funding (self): PTC Therapeutics; Research grant / Funding (institution): Regeneron; Research grant / Funding (institution): Agenus; Leadership role, Chair: NRG Oncology OVarian Committee; Leadership role, Associate Director: GOG Partners. D. Berg: Full / Part-time employment: Kazia Therapeutics Limited. J. Garner: Leadership role, Shareholder / Stockholder / Stock options, Full / Part-time employment, Officer / Board of Directors: Kazia Therapeutics Limited. D. Dizon: Research grant / Funding (institution): Bristol-Myers Squibb; Research grant / Funding (institution): Kazia Therapeutics; Honoraria (self): AstraZeneca; Honoraria (self), Advisory / Consultancy: Tesaro; Honoraria (self): Regeneron; Advisory / Consultancy: iMab. All other authors have declared no conflicts of interest.